Analysis of Capital Structure Determinants in Manufacturing Companies: Integration of Emerging Market Contextual Factors - Lilik Purwanti; Roekhudin; Anita Wijayanti; Aryo Prakoso; Melinda Ibrahim; Syarifah Nurhalisa Alattas (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2026)
Capital structure theory has developed substantially over time; however, its applicability to emerging markets characterised by funding constraints, such as Indonesia, remains insufficiently explored. Market frictions and institutional limitations may weaken the explanatory power of traditional frameworks, including the pecking order and trade-off theories, in explaining firms’ financing decisions. This study examines the determinants of capital structure in an emerging market context and identifies the need for theoretical refinement. Using panel data from 86 manufacturing firms listed on the Indonesia Stock Exchange over the 2019–2023 period and employing a panel regression estimated through a Partial Least Squares approach, the results show that profitability has a significant negative effect on capital structure, while share capital, debt tax shields, and firm size do not exert a statistically significant influence. Notably, the analysis reveals a positive relationship between business risk and leverage, which contradicts conventional theoretical predictions. This finding provides empirical support for the need to reformulate capital structure theory to better reflect the characteristics of emerging markets, particularly those facing capital market constraints.